Bacteriology primer in air contamination control - Kingsley, V. Victor (University of Toronto Press, 1967)
This primer is directed to air contamination control personnel, air engineers, whose only contact with bacteriology is usually their responsibility for providing "white" surroundings in industry and research. Professor Kingsley provides most basic information and describes problems in bacteriology which would help in the understanding, handling, and moving of "clean" (uncontaminated) air to and from critical areas. Divided into three parts, the manual includes sections on "Basic Principles of Bacteriology," "Bacteriology in the Air" and "The Sampling of Airborne Microorganisms." A glossary of bacteriological terms and graphs supplements the text.